HUBUNGAN ANTARA PENGATURAN DIRI DALAM BELAJAR (SELF REGULATED LEARNING) DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR INSTALASI TENAGA LISTRIK KELASI XII SMK PATRIOR 1 BEKASI - Sandy Maulana; Daryanto; Nur Hanifah Yuninda (Journal of Electrical Vocational Education and Technology, 2019)
The Relationship between Self-Arrangement in Learning, and Learning Motivation with Student Learning Outcomes Class XII TITL SMK Patriot 1 Bekasi. Essay. Electrical Engineering Education Study Program, Faculty of Engineering, Jakarta State University. 2019. Advisor: Dr. Daryanto, MT, Nur Hanifah Yunida, ST., MT. Self Regulated Learning is known as metacognition that works on learning processes that are equipped with learning planning, learning, and evaluating learning outcomes. Motivation Learning is a mental force to carry out activities in order to meet expectations and encouraging in this case is the purpose of learning. Learning Outcomes are changes that students have after receiving a learning experience that can be taken and learned in the form of knowledge, skills, attitudes, information, strategies and cognitive. The purpose of this study was to study the Relationship between Self-Arrangement in Learning and Learning Learning Motivation with Student Learning Outcomes Class XII TITL SMK Patriot 1 Bekasi. This research is a quantitative study with a correlative descriptive research design. The population in this study was the students of the TITL Vocational School Patriot 1 Bekasi class of 2018/2019. The sample of this research was 30 students of TITL SMK Patriot 1 Bekasi in 2018/2019. Self Regulated Learning (X1) and learning motivation (X2) research data were taken by filling in the research instrument containing a questionnaire and the Learning Outcomes (Y) research data was taken from the grades of class XII UAS students on electric power installation subjects. The data is stated validity and reliability, then the data are analyzed through normality test, linearity test, regression analysis, coefficient analysis, and significance test with t-test and f-test with a significance level of 5%. The conclusions between X1 and Y obtained coefficient ryx1 analysis = 0.599, significance coefficient obtained tcount (3.95)> ttable (2.05) with a contribution of 35.8%, while between X2 and Y obtained coefficient ryx2 analysis = 0.519, test significance coefficient obtained tcount (3.20)> ttable (2.05) with a contribution of 26.9%. and for the relationship X1 X2 and Y, the value of ryx1x2 = 0.618 is obtained, then the value of fcount = 8.34> ftabel = 3.35, which means fcount> ftabel, so it can be broadcast related to a positive and significant relationship. Class XII TITL SMK Patriot 1 Bekasi.